Variabilitas mean arterial pressure dan pulse pressure intraoperatif pada sectio caesarea dengan anestesi spinal - Maria Faustin Fickyyanti Sin; Pius Almindu Leki Berek; Maria Fatimah Wilhelmina Abuk Fouk; Christina Anugrahini (Holistik Jurnal Kesehatan, 2026)
Background: Spinal anesthesia for cesarean section often causes significant hemodynamic changes due to sympathetic blockade. Mean arterial pressure (MAP) and pulse pressure (PP) are important parameters in assessing perfusion, but their sensitivity in detecting intraoperative changes is not fully understood. Purpose: To analyze the variability of MAP and PP at various time points during a cesarean section procedure under spinal anesthesia. Method: This study used an observational design with a longitudinal approach in 90 cesarean section patients. The study was conducted in the operating room of a referral hospital (e.g., a regional general hospital in East Nusa Tenggara). Hemodynamic parameters were measured preoperatively, at baseline (0 minutes), and at 5, 10, 15, 20, 25, and 30 minutes intraoperatively. Data were analyzed using the Friedman test to assess differences between time points, followed by the Wilcoxon signed-rank test with Bonferroni correction for post hoc analysis. Results: Significant hemodynamic changes occurred throughout the intraoperative period. MAP showed a progressive decline starting at 5 minutes and reaching its lowest point at 20 minutes before gradually recovering. In contrast, PP showed less variation and a relatively stable pattern of change. Inferential analysis revealed significant differences in MAP and PP over time (p < 0.001), with greater variation in MAP. Post hoc analysis identified that the decline in MAP began significantly at 5 minutes and continued until its lowest point, while PP changes tended to be more fluctuating and less consistent. Conclusion: Spinal anesthesia for cesarean section causes significant hemodynamic changes, with a dominant decrease in MAP in the early intraoperative phase. MAP proved to be more sensitive than PP in detecting changes in systemic perfusion, making it more relevant as a primary parameter in intraoperative monitoring. These findings emphasize the importance of close monitoring and early intervention to prevent hypotension and maintain hemodynamic stability.   Keywords: Arterial Pressure; Cesarean Section; Intraoperative Hemodynamics; Pulse Pressure; Spinal Anesthesia.